Using of the Modern Information Technologies in Libraries: Problems and Solutions (Texas Journal of Philology, Culture and History, 2023)
The article is devoted to the analysis of important changes that are taking place in the field of creating and using of automation tools for information and library technologies and information resource management. Some practical solutions are shown on the example of the “MegaPro” Integrated Library System.